Quinoxaline derivatives as photoinitiators in UV-cured coatings - Balta, Demet Karaca; Keskin, Sevnur; Karasu, Feyza; Arsu, Nergis (ELSEVIER SCIENCE SA, 2007)
Photopolymerization of multifunctional acrylates with a series of quinoxaline derivatives as photoinitiator with N-methyldiethanol amine (MDEA) has been investigated by real-time Fourier transform infrared spectroscopy (RT-FTIR). The formulations were also coated onto tracing paper and cured by using Mini-UV-Cure unit. Curing was assessed until no visible deformation was observed. MEK resistance of films was also determined. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: quinoxalines; photoinitiators; RT-FTIR; UV-curing; FREE-RADICAL POLYMERIZATION; ELECTRON-TRANSFER; Chemistry; Materials Science